ANALISIS EFEKTIVITAS APLIKASI MONGGO LAPOR PADA PENINGKATAN PELAYANAN PUBLIK DI KOTA MAGELANG - Pertiwi, Putri Ika (Jendela Inovasi Daerah, 2025)
In order to realize its commitment to becoming a smart city, Magelang City has developed various digital innovations to accelerate the government's response to the needs of its citizens. One of the featured applications developed is "Monggo Lapor". This application serves as a public reporting medium for submitting complaints, criticisms, suggestions, and service requests directly and in real-time. This study uses a descriptive qualitative approach with data collection techniques through interviews, observation, and documentation. Research informants consisted of government officials managing the application and community service users. Data analysis used the Miles and Huberman interactive analysis model which includes data reduction, data presentation, and drawing conclusions. The results show that the Monggo Lapor application has proven effective in improving the quality of public services in Magelang City. This is evidenced by the fast and responsive response, reports that are always followed up to completion, the application is relatively easy to use by the public, and increased public participation in January - June 2025. This application plays a significant role in strengthening the transparency and responsiveness of public services. It is recommended that the Magelang City Government conduct more intensive digital literacy and outreach regarding the Monggo Lapor application, as well as socialize to the public that public reporting is a guaranteed citizen right and will be responded to openly and responsibly by the government.